Anomalous left coronary artery from the pulmonary artery: Outcomes and management of mitral valve - Yu, Juemin; Ren, Qiushi; Liu, Xiaobing; Chen, Tianyu; Liufu, Rong; Wen, Shusheng; Chen, Jimei; Cen, Jianzheng; Zhuang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Objective: Use of concomitant mitral valve repair remains controversial in anomalous left coronary artery from the pulmonary artery (ALCAPA) with mitral regurgitation (MR). This study aimed to evaluate postoperative mitral valve function and explore the indication for concomitant mitral valve repair. Methods: The medical records of 111 patients with ALCAPA and MR who underwent ALCAPA surgery between April 2006 and November 2020 were reviewed. The patients were categorized into three groups for comparison: group I consisted of 38 patients with trivial or mild MR and only underwent ALCAPA repair; group II comprised 37 patients with moderate or severe MR who similarly had only surgery of the ALCAPA performed; and group III comprised 36 patients who had concomitant mitral valve repair for moderate or severe MR. Result: Overall mortality was 7.2% (8 of 111). The mortality of group II (16.2%, 6 of 37) was higher than those of group I (5.3%, 2 of 38) and III (0%, 0 of 36) (p=0.027). All three patients who underwent mitral valve re-intervention were in group II. At the last follow-up, no patient had more than moderate MR in group I. The percentage of patients in whom the MR grade improved was 79.4% (27 of 34) in group III and 51.4% (19 of 37) in group II (p=0.001). The multivariable logistic regression revealed that patients who had concomitant mitral valve repair (Adjusted odds ratio=4.492, 95% CI: 1.909–12.794; p<0.001) was the major factor influencing MR grade improvement. Conclusions: The long-term outcomes after ALCAPA repair were favorable. For mild MR, ALCAPA repair only can be performed. For moderate and severe MR, we suggest concomitant mitral valve repair.